f(5+5)=f(5)+f(5)

Simple and best practice solution for f(5+5)=f(5)+f(5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(5+5)=f(5)+f(5) equation:


Simplifying
f(5 + 5) = f(5) + f(5)

Combine like terms: 5 + 5 = 10
f(10) = f(5) + f(5)

Reorder the terms for easier multiplication:
10f = f(5) + f(5)

Reorder the terms for easier multiplication:
10f = 5f + f(5)

Reorder the terms for easier multiplication:
10f = 5f + 5f

Combine like terms: 5f + 5f = 10f
10f = 10f

Add '-10f' to each side of the equation.
10f + -10f = 10f + -10f

Combine like terms: 10f + -10f = 0
0 = 10f + -10f

Combine like terms: 10f + -10f = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 10y=7y+21 | | x^2+y^2=90 | | 2(11+2x)+2(19+2x)=76 | | (x+4)2+112=0 | | f(5+5)= | | abs(10+2x)=16 | | -6X+-36+2=-6x+-3 | | x^2+(x+8)=40 | | 2(5x+6)=10x | | 45-48x=30x+40 | | 3a-5=(-14) | | 4(r+6)+36=2(2r+40) | | 8j-5=46 | | 60+50.45x=0+57.95 | | 9+4x=428 | | 7y-15=-1 | | y-9=-5(x+6) | | 3(9y+3)-11=2y+21 | | -6X+-36=-6x+-3 | | 2x+(3+4)=52 | | ax+d=c-bx | | 60n=(-12) | | -6X+36+2=-6x+-3 | | x+b=c-z | | 9a-(-72)=-8 | | -6=3y-21 | | 4k=-2k+18 | | 8=cups | | (0.25)X-1=32 | | 10e-6=14 | | 5.23x+10.46=20.92 | | 7+5x-3x=13 |

Equations solver categories